2014
DOI: 10.1111/anu.12106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary chitosan on growth performance, haematology, immune response, intestine morphology, intestine microbiota and disease resistance in gibel carp (Carassius auratus gibelio)

Abstract: A 75-day experiment was conducted with juvenile gibel carp (Carassius auratus gibelio) (4.80 AE 0.01 g) to evaluate effects of dietary chitosan on fish growth performance, haematology, intestine morphology and immune response. Six isonitrogenous (crude protein: 383 g kg À1 ), isolipid (97.5 g kg À1 ) and isocaloric (gross energy: 16.7 kJ g À1 ) diets were formulated to contain 0, 1800, 4000, 7500, 10 000, 20 000 mg kg À1 chitosan, respectively. The results showed that the growth was depressed when the fish fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 68 publications
(121 reference statements)
6
45
1
1
Order By: Relevance
“…The profile of plasma metabolites observed herein were within reference values determined for European seabass (Chen et al, 2014;Shiau and Yu., 1999). Chitosan has been reported to interfere with cholesterol absorption by binding with lipid (cholesterol) micelles, inhibiting their absorption, and increasing bile acid excretion (Khoushab and Yamabhai, 2010).…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…The profile of plasma metabolites observed herein were within reference values determined for European seabass (Chen et al, 2014;Shiau and Yu., 1999). Chitosan has been reported to interfere with cholesterol absorption by binding with lipid (cholesterol) micelles, inhibiting their absorption, and increasing bile acid excretion (Khoushab and Yamabhai, 2010).…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…Several reports have documented the immune stimulatory activity of chitin and/ or chitosan in fish, including rainbow trout, Oncorhynchus mykiss (Sakai, Kamiya, Ishii, Atsuta, & Kobayashi, 1992), gilthead sea bream, Sparus aurata L. (Esteban, Cuesta, Ortuno, & Meseguer, 2001), common carp, Cyprinus carpio (Gopalakannan & Arul, 2006) and olive flounder, Paralichthys olivaceus (Cha, Lee, Song, Lee, & Jeon, 2008). Also, optimal dietary chitosan enhanced lipid metabolism and immune competence and protects from pathogen invasion of the gibel carp, Carassius auratus gibelio, while low-dose dietary chitosan did not have an effect on the growth of fish and gibel carp, Carassius auratus gibelio (Chen et al, 2014). Dietary chitosan supplementation improved the growth performance and meat quality status of tilapia (Najafabad, Imanpoor, Taghizadeh, & Alishahi, 2016;Wang & Li, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that dietary chitosan at a moderate concentrations (4 and 7.5 g kg −1 diet) is recommended for the best growth performance, haematology and intestine morphology of gibel carp (Chen et al . ). Geng et al .…”
Section: Chitin the Main Producer Of Chitosanmentioning
confidence: 97%
“…In another study, six diets were formulated to contain 0, 1.8, 4, 7.5, 10 and 20 g chitosan kg À1 diet and then fed to juvenile gibel carp (Carassius auratus gibelio). The results showed that dietary chitosan at a moderate concentrations (4 and 7.5 g kg À1 diet) is recommended for the best growth performance, haematology and intestine morphology of gibel carp (Chen et al 2014). Geng et al (2011) found that 6.0 g chitosan kg À1 diet in combination with 1.0 g Bacillus subtilis kg À1 diet was ideal for optimum growth of cobia (Rachycentron canadum).…”
Section: Effect Of Chitosan On Growth Performancementioning
confidence: 99%